Testing the Law of One Price on Exports of Tropical Forest Products: A Co-integration Approach - Baharumshah, Ahmad Zubaidi; Habibullah, Muzafar Shah (Universiti Putra Malaysia Press, 1995)
Trade theory often postulates the existence of a representative price, that is, a single price that prevails in all markets. This is known as the Law of One Price (LOP). In this paper the empirical validity of LOP was tested using the recently developed co-integration method for timber exports. Monthly data for the period January 1985 to December 1992 were used to analyse the long-run equilibrium relationship. Empirically, we found the exchange rate pass-through on the exports to be complete for all timber products and markets. The results obtained suggest that the data are consistent with the LOP as a long-run relationship. We conclude that the markets for tropical forest products are generally competitive.